Pengembangan Kawasan Pertanian Tanaman Hortikultura Kabupaten Bangka Selatan dengan Analisisis Quantum Geographic Information System (QGIS) - Purnama, Eriko; Firdaus, Luhung Amin; Setiawan, Fahri (Universitas Galuh, 2024)
This research aims to map potential agricultural land in South Bangka Regency, Bangka Belitung Islands Province using Quantum Geographical Information System (QGIS). The method used in this research is a descriptive method to analyze and match data on the condition of the study area with land capability class criteria referring to the Decree of the Minister of Agriculture of the Republic of Indonesia Number 472/Kpts/RC.040/6/2018 concerning the Location of National Agricultural Areas so that in the development of horticultural crops is not yet optimal. This is also in line with the Decree of the Regent of South Bangka Number: 188.45/237/DPPP/2020 concerning the Determination of Horticultural Areas in South Bangka Regency to accelerate increased production, productivity, added value and exports of agricultural commodities, as well as the welfare of farmers and development of agricultural areas with a whole regional approach. The parameters observed include data on existing and potential horticultural areas. The research results show that the existing recorded commodities with potential consist of avocado, onion, spinach, chili, duku, durian, ginger, guava, guava, orange, kangkong, turmeric, laos, mango, mangosteen, pineapple, jackfruit. , papaya, banana, rambutan, zalacca, mustard greens, sapodilla, non-chili and onion SBS, watermelon, eggplant, cucumber and melon. The following is the total area of existing and potential proposals in South Bangka Regency.